Response of Best Management Practices on Growth, Productivity and Profitability in Fenugreek (Trigonella foenum-graecum L.) under Transitional Plain of Luni Basin of Rajasthan - Parewa, H. P.; Jain, L. K.; Bhardwaj, R. L.; Choudhary, R. N.; Kumar, M.; Choudhary, A.; Sirohi, R. (International Journal of Bio-resource and Stress Management, 2025)
The field experiments were conducted during rabi (November–March, 2018–19 and 2019–2020) with Trigonella foenum-graecum L. sown at Agricultural Research Sub-station Sumerpur, Pali, Agriculture University, Jodhpur, Rajasthan, India to investigate the impact of treatments on growth, productivity and economics of Trigonella foenum-graecum L. There were ten treatments namely control (T1), 50% RDF (T2), 75% RDF (T3), 100% RDF (T4), 50% RDF+Vermicompost at 2 t ha-1 (T5), 75% RDF+Vermicompost at 2 t ha-1 (T6), 50% RDF+Vermicompost at 2 t ha-1+Rhizobium at 2.5 kg ha-1+PSB at 2.5 kg ha-1 (T7), 75% RDF+Vermicompost at 2 t ha-1+Rhizobium at 2.5 kg ha-1+PSB at 2.5 kg ha-1 (T8), 50 % RDF+Vermicompost at 2t ha-1+Seed treatment with Rhizobium at 600 g ha-1+PSB at 600 g ha-1 (T9) and 75 % RDF+Vermicompost at 2 t ha-1+Seed treatment with Rhizobium at 600 g ha-1+PSB at 600 g ha-1 (T10) replicated three times and arranged in a randomized block design (RBD). The treatment consisting combination of 75% RDF+VC at 2 t ha-1+ bioinoculants significantly improved the status of organic carbon, available N and P of soil after harvest of the crop. Among the integrated treatments, application of 75% RDF+VC at 2 t ha-1+bioinoculants recorded maximum productivity (1.65 t ha-1). The treatment T4 (100% RDF) provided highest B:C ratio (2.88) followed by treatment T10 (2.60) and T8 (2.58) which were at par with the 100% RDF. Overall, the study concluded that 75% RDF along with 2 t ha-1 vermicompost and bioinoculants optimized fenugreek yield, improved soil fertility and increased profitability.